2018
DOI: 10.1371/journal.pone.0192772
|View full text |Cite
|
Sign up to set email alerts
|

Elevated temperature drives kelp microbiome dysbiosis, while elevated carbon dioxide induces water microbiome disruption

Abstract: Global climate change includes rising temperatures and increased pCO2 concentrations in the ocean, with potential deleterious impacts on marine organisms. In this case study we conducted a four-week climate change incubation experiment, and tested the independent and combined effects of increased temperature and partial pressure of carbon dioxide (pCO2), on the microbiomes of a foundation species, the giant kelp Macrocystis pyrifera, and the surrounding water column. The water and kelp microbiome responded dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
124
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(130 citation statements)
references
References 82 publications
6
124
0
Order By: Relevance
“…Based on these cases it seems likely that also the macrophyte microbiome is linked to environmental tolerance, including warming. The only study that combined elevated temperatures and ocean acidification showed that elevated temperatures alone drives dysbiosis in Macrocystis pyrifera under which kelp growth was also negatively affected (Minich et al, 2017). However, acidification counteracted the elevated temperature effects resulting in positive kelp growth and a commensal microbial community that increased mucus production (Minich et al, 2017).…”
Section: A3 Marine Macrophyte Holobionts and Their Hologenomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these cases it seems likely that also the macrophyte microbiome is linked to environmental tolerance, including warming. The only study that combined elevated temperatures and ocean acidification showed that elevated temperatures alone drives dysbiosis in Macrocystis pyrifera under which kelp growth was also negatively affected (Minich et al, 2017). However, acidification counteracted the elevated temperature effects resulting in positive kelp growth and a commensal microbial community that increased mucus production (Minich et al, 2017).…”
Section: A3 Marine Macrophyte Holobionts and Their Hologenomesmentioning
confidence: 99%
“…The only study that combined elevated temperatures and ocean acidification showed that elevated temperatures alone drives dysbiosis in Macrocystis pyrifera under which kelp growth was also negatively affected (Minich et al, 2017). However, acidification counteracted the elevated temperature effects resulting in positive kelp growth and a commensal microbial community that increased mucus production (Minich et al, 2017). Although it is not clear whether the microbiome changes in reaction to a change in the health of the host or vice versa (probably a tight and complex interaction of the two), it is increasingly clear that the interaction of global change factors on marine macrophytes and their microbiomes should be more investigated.…”
Section: A3 Marine Macrophyte Holobionts and Their Hologenomesmentioning
confidence: 99%
“…The significant differences in carbon and nitrogen biogeochemistry that we measured inside vs. outside of the kelp bed coincided with the strongest microbial contrasts. Kelp-bed-enriched taxa included Flavobacteriaceae, which are often hosted by Macrocystis (Michelou et al 2013, Vollmers et al 2017, Minich et al 2018, are usually aerobic (McBride 2014), and were also an abundant component in the Monterey Bay, California kelp bed (Wilson et al 2018). All nine taxa that had a significantly greater relative abundance inside kelp beds were found on either Nereocystis or Macrocystis in a study of surface-associated microbes (Weigel and Pfister 2019).…”
Section: Kelp Forests Entrain Distinct Microbial Communitiesmentioning
confidence: 99%
“…A number of environmental variables showed an interaction between site and whether the sampling occurred in or outside of the kelp bed, and this interaction was always due to a greater difference between the inside and the outside of the bed at Tatoosh (Tables 1-3). Microbes in association with Macrocystis were enriched in nitrogen metabolic functions compared to surrounding seawater (Minich et al 2018), which may contribute to increased nitrogen recycling and the pattern of increased 15 N NH4 within the kelp bed. Kelp-bed-enriched taxa included Flavobacteriaceae, which are often hosted by Macrocystis (Michelou et al 2013, Vollmers et al 2017, Minich et al 2018, are usually aerobic (McBride 2014), and were also an abundant component in the Monterey Bay, California kelp bed (Wilson et al 2018).…”
Section: Kelp Forests Entrain Distinct Microbial Communitiesmentioning
confidence: 99%
See 1 more Smart Citation